ANALISIS PERBANDINGAN PENGATURAN PEMUTUSAN HUBUNGAN KERJA (PHK) DAN PENYELESAIAN PERSELISIHAN KARYAWAN TETAP (PKWTT)DI INDONESIA DAN SINGAPURA - Ridwan Amarulloh; Rumainur (JOURNAL OF LAW AND NATION, 2024)
Labor is an important component in a country's industrial wheels. Legal certainty governing labor rights is very necessary to protect workers' interests and ensure harmonious working relationships. Regulations on Termination of Employment Relations (PHK) and Settlement of Permanent Employee Disputes (PKWTT) in Indonesia adhere to the Civil Law legal system, while Singapore adheres to the legal tradition. Common Law. The differences are reflected in the legal regulations and dispute resolution procedures in the two countries. This research is normative juridical legal research using comparative legal methods. Therefore, the data source used is a secondary data source collected using library research techniques. After the data is collected, the data is processed and analyzed using descriptive qualitative analysis methods, meaning that the data is grouped based on the aspects studied, then conclusions are drawn and explained descriptively. Based on the research results, both countries have similarities in the types of Termination of Employment Relations (PHK), but in dispute resolution there are differences, in Settlement of disputes Termination of Employment Relations (PHK) in Indonesia is generally through non-litigation channels (mediation, conciliation, arbitration) or litigation (Industrial Relations Court) whereas in Singapore there is more emphasis on resolving disputes through non-litigation channels, such as mediation and arbitration.